The use of mouthwashes as an adjunct to non-surgical periodontal treatment in patients with Type 2 Diabetes mellitus: Literature review (Research, Society and Development, 2023)
Type 2 diabetes mellitus is a systemic disease which produces high levels of glucose in the blood since there is a deficiency or a decrease in the hormone insulin, this disease affects the quality of life of the patient who suffers from it. Multiple studies have linked type 2 diabetes to periodontal disease since it alters the patient's immune response, thus affecting the dental attachment complex; Despite the complications involved in coping with this disease, multiple periodontal treatments have been developed that help reduce symptoms, such as non-surgical periodontal therapy with scaling and root planing, although this type of therapy is very effective, the study carried out has as objective to gather information about how mouthwashes serve as coadjuvants in therapy and how these substances can help not only reduce periodontal disease but also improve the quality of life of patients suffering from type 2 diabetes mellitus.